Expression of Her-2/NEU in Patients With Primary Non-small Cell Lung Cancer (Nsclc) - Sharmin, Rumana; Sharmin, Shegufta; Mudi, Nondita; Abedin, Mohammed Raisul; Hoque, Mohammad Mahfuzul; Kabir, Enamul (Journal of Dhaka Medical College, 2023)
Introduction: Now a days immunohistochemistry and genomic testing for patient with Non- Small Cell Lung Cancer (NSCLC) is becoming new standard of care in clinical decision making. A renewed interest has been emerging on the human epidermal growth factor-2 (HER2) pathway. Aim of this present study was clinicopathological correlation of HER-2/neu expression by IHC in NSCLC. Method: This was a Cross sectional and observational study done at Sir Salimullah Medical College and National Institute of Disease of the Chest and Hospital (NIDCH) and other private hospitals in Dhaka city during July / 2014 to June / 2016. Adult of both gender with histologically diagnosed as a case of NSCLC was include in the study. Immunohistochemistry was done to see the positivity for HER/neu and clinical characteristics were observed. Result: A total 45 patients with NSCLC were enrolled in the study. Male was 77.8% (n=35) and female was 22.2% (n=10). The mean age was 55.67 (SD± 12) years and mean age of male was higher compared to female (57.54±11.64 years verses 49.1±11.38 years). Most of the male were smokers (71.1%) and female were nonsmokers (90%). 57.78% (n=26) of patients and 42.22% (n=19) of patients had adenocarcinoma and squamous cell carcinoma respectively. Most squamous cell carcinoma patients were elderly, had wasting and having higher TNM staging. Serum LDH level was higher with advance staging and grading. Only 8.89% (n=4) had HER-2/neu positive expression affected by male. Patients with HER 2/neu positive expression were relatively older (mean age 62.5±17.08). However, there were equal in histopathological categorization (50% SCC and 50% Adenocarcinoma). Mean LDH was slightly higher in HER-2 positive patients was compared to HER-2 negative patients (569.5±232.6 versus 469.7±181.8). Conclusion: About nine percent of patients having HER-2/neu positive was relatively older and had more high level of LDH. A large-scale study should be conducted in Bangladeshi population to characterize epidemiological, clinicopathological feature in patients with NSCLC with HER-2 expression. J Dhaka Med Coll. 2021; 29(1): 99-110